Second-Line Treatment of Advanced Urothelial Cancer with Paclitaxel and Everolimus in a German Phase II Trial (AUO Trial AB 35/09) - Niegisch, Guenter; Retz, Margitta; Thalgott, Mark; Balabanov, Stefan; Honecker, Friedemann; Ohlmann, Carsten Henning; Stoeckle, Michael; Boegemann, Martin; Vom Dorp, Frank; Gschwend, Juergen; Hartmann, Arndt; Ohmann, Christian; et al. (Oncology, 2015)
The efficacy of second-line treatment after failure of platinum-based chemotherapy in patients with advanced urothelial cancer is limited. Based on encouraging preclinical and clinical phase I data, we evaluated the safety and efficacy of the combination of paclitaxel and everolimus in these patients.In this trial, patients having failed to respond to prior platinum-based combination treatment of urothelial cancer were treated with paclitaxel (175 mg/m(2) i.v., 3-weekly) and the mTOR-inhibitor everolimus (10 mg p.o., once daily). The patients were treated until tumor progression or until a maximum of 6 cycles was completed. A one-stage design was used to evaluate the objective response rate (ORR) as the primary endpoint.A total of 27 patients (67% male; median age 63 years) were enrolled. The most frequent grade III/IV toxicities were anemia (28%), peripheral neuropathy (28%), and fatigue (24%). No treatment-related deaths were reported. Complete and partial remissions were observed in 0/24 and 3/24 patients eligible for efficacy analysis, respectively (ORR 13%). Progression-free survival was 2.9 months [95% confidence interval (95% CI) 1.9-4.2], and the median overall survival was 5.6 months (95% CI 4.8-10.2).The combination of paclitaxel and everolimus has not achieved the expected efficacy in second-line treatment of urothelial cancer and should not be further explored.
EVALuna2:6790